Palm oil a saturated fat: a case of incidental or tactical classification / Arshad Hashim - Hashim, Arshad (Universiti Teknologi MARA Cawangan Pahang, 1996)
This work was based on my original paper titled "The Technical Characteristics of Palm Oil", rewritten and revised after helpful comments made by Professor W P T James, Director of Rowell Research Institute, United Kingdom and Chairman of the European Advisory Group on Palm Oil. The new title was given to suit the new objectives and problems presented in this paper. The remaining errors and other shortcoming are mine alone.